Development of BSM Interactive Multimedia Based on Construct 2 as an English Language Learning Media for Grade 3 - Muchammad Wahyu Chabibullah; Rohmat Hidayat; Moh Faridl Darmawan (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This study aims to develop learning media in the form of an Android-based English educational game. For the presentation of the material using English subjects for class 3 MI, such as names of vegetables, fruits, animals, and colors. The development of learning media uses software construct 2 as an application for making English educational games. Learning media testing was carried out by 13 students of class 3 MI Mamba'ul Ma'arif. Data was collected by distributing test result questionnaires and response questionnaires. The research method used is the ADDIE method, by applying several stages, namely the first Analysis (analysis), the second Design (design), the third Development (development), the fourth Implementation (implementation), and the fifth Evaluation (evaluation). The results of the feasibility test of the material expert learning media show that it is very feasible by obtaining a value of 4.5. Media experts show it is very feasible with a score of 4.3. And the results of student trials obtained an average test score of 80.7, test 2 of 83.4, and test 3 of 91.1. Based on these results, it can be concluded that the learning media in the form of educational games is very interesting and suitable to be used to help students learn grade 3 MI.